Notes on the genus Conocephalus (Orthoptera: Tettigoniidae; Conocephalinae; Conocephalini) from India and description of two new species - Nagar, Rajendra; Swaminathan, R. (Zootaxa, 2016)
The present paper describes two new species of Conocephalus: Conocephalus decaspinosus sp. nov. and C. kwasiphaiensis sp. nov., as additions to the previously known species of the genus; among these, two species have been reported for the first time from India, viz., C. concolor peneri and C. vaginalis. The key morphological characters of the head, pronotum, cerci, spines on the fore tibiae, hind femora, stridulatory file and the ovipositor have been illustrated with suitable line drawings to distinguish the reported new species. The distribution map of the species in India has been provided with a key to the subgenera.